SUGBUANONG BINISAYA: A MEDIUM OF INSTRUCTION FOR GRADE TWO PUPILS - Erwin R. Bucjan; Mardie E. Bucjan (EPRA International Journal of Research and Development (IJRD), 2022)
Mother tongue as first language is the language a person is exposed to and acquired during the early years of child-hood and which normally becomes his natural instrument of thought and communication according to UNESCO, 1953 as cited by Charanchi (2011). The study focuses on the perception of the teachers, pupils and parents in the use of Sugbuanong Binisaya as medium of instruction and use Sugbuanong Textbooks provided by DepEd; the necessity of Mother Tongue or the Sugbuanong Binisaya as a medium of instruction; the language preference of the pupils and teachers as a medium of instruction; and the problems met by the teachers, pupils and parents in the implementation of mother tongue education. The study used a quantitative and qualitative research. The instrument was adopted from the study of Afzal Shadi (2013). It was revised and translated into Filipino language to answer the objectives of the current study. A mean and percentage score was utilized to analyze the data. The grade 2 teachers and grade 2 pupils were the subject of the study. Based on the findings of the study, the use of Sugbuanong Binisaya in the teaching and learning in the classroom is not effective because both teachers and pupils found difficulty in using the language. Therefore, the use of Sugbuanong Binisaya as MTB-MLE in grade 2 pupils of Falcon Memorial Elementary School shall be definitely suspended because it does not help pupils to develop their skills particularly speaking, writing, listening and reading. Hence, it is the hindrance to grade 2 pupils’ and teachers’ understanding.